Effects of Extreme Salinity Stress on a Temperate Mangrove Ecosystem - Dittmann, Sabine; Mosley, Luke; Stangoulis, James; Nguyen, Van Lam; Beaumont, Kieren; Dang, Tan; Guan, Huade; Gutierrez-Jurado, Karina; Lam-Gordillo, Orlando; McGrath, Andrew (Frontiers in Forests and Global Change, 2022)
Mangrove forests provide essential ecosystem services, but are threatened by habitat loss, effects of climatic change and chemical pollutants. Hypersalinity can also lead to mangrove mortality, although mangroves are adapted to saline habitats. A recent dieback event of >9 ha of temperate mangrove (Avicennia marina) in South Australia allowed to evaluate the generality of anthropogenic impacts on mangrove ecosystems. We carried out multidisciplinary investigations, combining airborne remote sensing with on-ground measurements to detect the extent of the impact. The mangrove forest was differentiated into “healthy,” “stressed,” and “dead” zones using airborne LIDAR, RGB and hyperspectral imagery. Differences in characteristics of trees and soils were tested between these zones. Porewater salinities of >100 were measured in areas where mangrove dieback occurred, and hypersalinity persisted in soils a year after the event, making it one of the most extreme hypersalinity cases known in mangrove. Sediments in the dieback zone were anaerobic and contained higher concentrations of sulfate and chloride. CO2 efflux from sediment as well as carbon stocks in mangrove biomass and soil did not differ between the zones a year after the event. Mangrove photosynthetic traits and physiological characteristics indicated that mangrove health was impacted beyond the immediate dieback zone. Normalized Difference Vegetation Index (NDVI), photosynthetic rate, stomatal conductance and transpiration rate as well as chlorophyll fluorescence were lower in the “stressed” than “healthy” mangrove zone. Leaves from mangrove in the “stressed” zone contained less nitrogen and phosphorous than leaves from the “healthy” zone, but had higher arsenic, sulfur and zinc concentrations. The response to extreme hypersalinity in the temperate semi-arid mangrove was similar to response from the sub-/tropical semi-arid mangrove. Mangrove in semi-arid climates are already at their physiological tolerance limit, which places them more at risk from extreme hypersalinity regardless of latitude. The findings have relevance for understanding the generality of disturbance effects on mangrove, with added significance as semi-arid climate regions could expand with global warming.